Das nationale Recht auf gute Verwaltung: Ein notwendiger Schritt zur Subjektivierung des deutschen Verwaltungsrechts? - Merkl, Simone (Tectum Verlag, 2023)
Does a right to good administration, as it already exists at Union level, make sense in the German legal order? In order to answer this question, the author firstly analyses Art. 41 EU CFR and the Code of Good Administrative Behaviour of the European Ombudsman's Office and contrasts the German with the EU administrative law system. On the other hand, taking into account subjectification tendencies, she fundamentally demonstrates that the understanding of good administration is relative and dependent on the understanding of administration. Simone Merkl worked for several years as a research assistant in teaching and researching administrative and EU law and currently advises federal, state and local authorities and their institutions as a lawyer.